Re-examining the Consistency of al-Māwardī’s Interpretative Method on Jināyāt Verses - Kamal Fiqry Musa; Achmad Zubairin; Eva Nugraha (AHKAM : Jurnal Ilmu Syariah, 2026)
Amid accusations of al-Māwardī’s theological alignment with the Muʿtazilite and criticisms that his interpretation of the jināyah (criminal law) verses contradicts human values, this study highlights the anthropocentric nature of his exegetical approach. By analyzing his commentary on jināyah verses, it demonstrates how he employs the tafsīr bi al-ma’thūr (tradition-based) method—relying on the hadith and accounts from the Prophet’s companions and the tābi’īn—which characterizes his work as tafsīr jam’i al-aqwāl (an eclectic method). In presenting the perspectives of the companions and classical scholars, al-Māwardī’s commentary shares similarities with that of al-Ṭabarī (though less comprehensive), Ibn al-Jawzī’s Zād al-Masīr, and al-Ṣābūnī’s Ṣafwah al-Tafāsīr. However, it diverges significantly from al-Ṣābūnī’s other work, Rawā’i‘ al-Bayān Tafsīr Āyāt al-Aḥkām. Furthermore, this research proves that al-Māwardī consistently applies the Shāfi‘ī method of legal deduction (istinbāṭ al-ḥukm), wherein legal rulings must fundamentally derive from the Quran, hadith, opinions of the companions, takhyīr (option), ijmā‘ (consensus), and istidlāl (inferential reasoning).   Abstrak Di tengah tudingan teologi al-Māwardī  yang menganut Muʿtazilah, dan metode penafsiran ayat-ayat jinayat-nya yang menurut sebagian kalangan bertentangan dengan nilai-nilai kemanusiaan,  artikel ini justru menyoroti metode penafsirannya yang antroposentris. Dengan menganalisis penafsirannya pada ayat-ayat jināyah melalui metode tafsir bi al-ma’thūr yang mendasarkan pada hadis dan riwayat para sahabat dan tābi’īn, tafsir al-Māwardī bercorak tafsīr jam’i al-aqwāl (metode eklektik). Tafsir al-Māwardī memiliki kesamaan dengan tafsir al-Ṭabarī, (meski tidak sekomprehensif al-Ṭabarī), tafsir Ibn al-Jauzī dalam kitab Zād al-Masīr, dan tafsir al-Ṣābūnī  dalam kitab Ṣafwah al-Tafsīr yang juga menghadirkan pendapat-pendapat sahabat dan ulama. Akan tetapi, tafsir ini berbeda dengan kitab al-Ṣābūnī dalam Rawāi’ al-Bāyān Tafsīr Āyāt al-Aḥkām. Penelitian ini juga membuktikan bahwa metode istīnbāṭ hukum yang digunakan al-Māwardī dalam penafsirannya secara konsisten menggunakan metode istinbāṭ al-ḥukm al-Shāfi’ī, yaitu penetapan suatu hukum didasarkan pada dalīl Al-Qur’an, Hadis, pendapat sahabat, takhyīr, ijmā’, dan istidlāl.